Institutional obstacles to South African entrepreneurship - Fred Ahwireng-Obeng; Desmond Piaray (South African Journal of Business Management, 1999)
Institutional risk factors exert a powerful negative influence on entrepreneurial investment decisions in South Africa. This conclusion emerges from a study of South African manufacturing and service sectors based on a previous one conducted on a world-wide scale by the World Bank in 1997. The South African study examines six institutional variables by sector-type and market-access and finds that entrepreneurs of young, small and non-exporting firms particularly perceive these institutional obstacles as a real problem most of the time. This observation compares closely with the World Bank's report on sub-Saharan Africa. There are several implications for the finding. Despite far-reaching institutional reforms much more will be required if South Africa's transition to a democratic polity and open, liberal economy is to yield the widely-expected post-apartheid dividends of rapid economic growth, high levels of employment and more equitable distribution of income and wealth. In the present circumstances, the country's prospective role as a growth-pole for Southern African regional development and the propelling force of an African renaissance is unlikely to materialise.
Keywords: 650